Dorsal striatum c-Fos activity in perseverative ephrin-A2A5−/− mice and the cellular effect of low-intensity rTMS - Tomar, Maitri; Rodger, Jennifer; Moretti, Jessica (Frontiers in Neural Circuits, 2023)
Overreliance on habit is linked with disorders such as drug addiction and obsessive-compulsive disorder and there is increasing interest in the use of repetitive transcranial magnetic stimulation (rTMS) to alter neuronal activity in the relevant pathways and for therapeutic outcomes. Here, we studied the brains of ephrin-A2A5-/- mice, which previously showed perseverative behaviour in progressive-ratio tasks, associated with low cellular activity in nucleus accumbens. We investigated if rTMS treatment had altered the activity of the dorsal striatum in a way which suggested altered hierarchical recruitment of brain regions from ventral to dorsal striatum, which is linked to abnormal habit formation. Brain sections from a limited number of mice that underwent training and performance on a progressive ratio task with and without low intensity rTMS (LI-rTMS) were taken from a previous study. We took advantage of the previous characterisation of perseverative behaviour to investigate the contribution of different neuronal subtypes and striatal regions within this limited sample. Striatal regions were stained for c-Fos as a correlate of neuronal activation, for DARPP32 to identify medium spiny neurons (MSNs), and for GAD67 to identify GABA-ergic interneurons. Contrary to our hypothesis, we found that neuronal activity in ephrin-A2A5-/- mice still reflected typical organization of goal-directed behavior. There was a significant difference in the proportion of neuronal activity across the striatum between experimental groups and control, but no significant effects identifying a specific regional change. However, there was a significant group by treatment interaction which suggests that MSN activity is altered in the dorsomedial striatum and a trend suggesting that rTMS increases ephrin-A2A5-/- MSN activity in the DMS. Although preliminary and inconclusive, the analysis of this archival data suggests that investigating circuit-based changes in striatal regions may provide insight into chronic rTMS mechanisms that could be relevant to treating disorders associated with perseverative behaviour.